2008
DOI: 10.1016/j.neuropsychologia.2007.12.011
|View full text |Cite
|
Sign up to set email alerts
|

The role of the orbitofrontal cortex in human discrimination learning

Abstract: Several lines of evidence implicate the prefrontal cortex in learning but there is little evidence from studies of human lesion patients to demonstrate the critical role of this structure. To this end, we tested patients with lesions of the frontal lobe (n = 36) and healthy controls (n = 35) on two learning tasks: the weather prediction task (WPT), and an eight-pair concurrent visual discrimination task ('Choose'). Performance of both tasks was previously shown to be disrupted in patients with Parkinson's dise… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 74 publications
(86 reference statements)
2
18
0
1
Order By: Relevance
“…Our results do not concur with this view as frontal regions and in particular the OFC, medial PFC and frontopolar cortex correlated with performance on the WPT as well. Our findings are therefore much more in line with other studies showing that lesions to the orbitofrontal cortex also significantly impairs performance on the WPT (Chase et al, 2008) as well as recent fMRI studies showing concurrent activations in striatal and frontal brain regions during WPT performance, including medial PFC and OFC activations (Aron et al, 2006; Poldrack and Foerde, 2008). …”
Section: Discussionsupporting
confidence: 92%
“…Our results do not concur with this view as frontal regions and in particular the OFC, medial PFC and frontopolar cortex correlated with performance on the WPT as well. Our findings are therefore much more in line with other studies showing that lesions to the orbitofrontal cortex also significantly impairs performance on the WPT (Chase et al, 2008) as well as recent fMRI studies showing concurrent activations in striatal and frontal brain regions during WPT performance, including medial PFC and OFC activations (Aron et al, 2006; Poldrack and Foerde, 2008). …”
Section: Discussionsupporting
confidence: 92%
“…In reward learning tasks, models suggest that the orbitofrontal cortex maintains recent reinforcement experiences in an active working memory-like state, which can govern trial-to-trial behavioral adjustments through top-down projections (Frank and Claus, 2006;Deco and Rolls, 2004). Supporting this interpretation, orbitofrontal patients show impairments in early phases of acquisition in reinforcement tasks (Chase et al, 2008), as do patients with schizophrenia (Waltz et al, 2007). Moreover, recent studies reported a gene-dose effect of COMT on orbitofrontal activity during reward receipt (Figure 2b) (Dreher et al, 2009) and in lateral PFC during reward anticipation (Dreher et al, 2009;Yacubian et al, 2007).…”
Section: Prefrontal Genetic Contributions: Comt and Drd4mentioning
confidence: 95%
“…The subsequent voxel-wise subtraction analysis showed that poor learners frequently had lesions in insular and striatal areas, but especially often within the inferior pre-frontal cortex (BA 10). Implicit learning is frequently impaired after prefrontal lesions (Barker et al, 2004, Chase et al, 2008 and probabilistic classification learning is facilitated by direct current stimulation of the prefrontal cortex (Kincses et al, 2004). The prefrontal cortex is thought to integrate information about the assumed value and prediction of outcomes into the processes of decision-making and the re-adjustment on this information based on related feedback (Liu et al, 2011).…”
Section: Discussionmentioning
confidence: 99%